Assembling Understandings - Emmanuel, Joy; Thompson, Matthew (University of Victoria Libraries, 2022)
With Assembling Understandings, the Canadian Social Economy Hub has developed a thematic summary of the CSERP outputs, exploring some of the dominant crosscutting themes within the research findings. This approach is very similar to a grounded theory approach wherein the authors, while reviewing the various available documents, ‘listened’ to the data for emerging themes. Care was taken to engage with the work from multiple angles, taking note of both diversity and unity within the body of research. The challenge in this form of research was for the authors to construct each chapter based on what was covered in the research as opposed to the expanse of what can be covered under each theme. In this way, the overall picture provided here is not a complete analysis of Canada’s social economy landscape, but rather provides an overview of the CSERP research findings in the following thematic areas: Mapping, Social Enterprise, Co-operatives, Indigenous Peoples, Organizational Governance & Capacity, Social Finance, and Public Policy. Each thematic area had representation in over 50 CSERP projects, with some chapters involving as many as 85 relevant research products. As a result, Assembling Understandings is a useful reference point for both reviewing the available CSERP documents and identifying where further research may be required.